Sayyid Mawdudi’s tafhim Al-Qur’an: Salient features - Osmani, Noor Mohammad (IIUM Press, International Islamic University Malaysia, 2017)
Sayyid Abu’l A`la Mawdudi’s Tafhim al-Qur’an is among the widely read tafsir of the Qur’an, which has already been translated into number of languages of the world. The main purpose of this study is to introduce the monumental tafsir of Mawdudi, evaluate its fundamental features, and present the basic principles and characteristics of Islamic Da`wah as advocated by Mawdudi and reflected in his tafsir of the Qur’an. The study also evaluates objectively the position of Tafhim al-Qur’an in the context of both traditional and modern tafsir literature, and tries to see how far the author is in agreement with the objectives of shari'ah, fundamentals of Islam and the prominent commentators of the Qur’an. This study adopts the approach of textual analysis in dealing with Mawdudi’s tafsir. It appreciates, acknowledges and sometimes critically evaluates the viewpoints of Mawdudi in his tafsir. The research depends basically on the tafsir of Mawdudi, his writings on various issues, traditional and modern tafasir and the fundamental sources of Islam. Sayyid Mawdudi felt a serious need for an easy-to-read tafsir to attract the common people towards understanding the Qur’an. The Qur’an, though the most widely read Book of the world, was in reality very much neglected in its application and implementation. Mawdudi’s Tafhim was able to change this attitude of Muslims to a great extent, and made them study the Qur’an not for mere blessings, but for understanding it properly and implementing it in their own socio-political life. Mawdudiincorporated the summary of his whole life experience and knowledge in this tafsir. He wrote it as a guidebook for those who devote their life to Allah and the cause of Islam.